Evaluation of the Apical Seal in Root Canals Prepared with Rotary ProTaper Files and Obturated by Different Methods - Sabah A Ismail; Wiaam M O Al-Ashou; Raghad A Al-Askary (University of Mosul, College of Dentistry, 2011)
Aims: The aim of this in vitro study was to evaluate the apical sealing ability of matched-taper Single-cone, Thermafil, and Cold lateral condensation obturations. Materials and Methods: Thirty-six ex-tracted human lower canine teeth were instrumented to size (F3) with ProTaper rotary instruments after cutting of their crowns to the cement-enamel junction CEJ. The working length was determined for each tooth. The teeth were divided into (3) groups (10) of each and (6) teeth were used as a positive and negative control groups. The teeth were obturated with matched-taper Single-cone, Thermafil, and lateral condensation techniques. Tgadseal was used as a root sealer in this study. A die penetration method was used to evaluate the apical seal using a stereomicroscope at 40X magnification. One-way analysis of variance and Duncan's tests were used for statistical analysis. Results: The statistical analysis of the results demonstrated that there was no statistically significant difference in microleakage between the lateral condensation and Thermafil groups. The matched taper single cone showed the least microleakage with a significant difference than the other two groups. Conclusions: The apical sealing ability of Matched-taper Single-cone obturation was better than the lateral condensation and Thermafil techniques when the root canal was prepared using a ProTaper rotary instrumentation.